MIGRASI ORANG BIAK KE PULAU BATANTA KAMPUNG AREFI KABUPATEN RAJA AMPAT - Rini Maryone (BALAI ARKEOLOGI PAPUA, 2010)
Archaeological studies, regarding the origin of the population can be observed from the material culture left behind. The discovery of archaeological data, especially prehistoric times, may provide clues to the approach or the analyst comparison with the findings of other cultural objects Similarly, with the origin of Biak. The existence of people residing on the island of Biak in Kampung Batanta Arefi, with penulusuran story myth and there is evidence that it can be concluded that the Biak people just immigrants or migration on the island.